مشاكل القواعد في ترجمة مجموعة قصة قصيرة "أرنى الله" لتوفيق الحكيم في موضوع الحب - Daud Lutfhian, Muhammad; Mahendra, Ahdiyat (Journal of Arabic Language and Literature (ALLAIS), 2023)
The problem in this research is the grammatical problem found in the translation of the short story collection of Arinillah by Taufik Hakim. This study aims to determine (1) the number of grammatical problems, (2) the types of grammatical problems, and to describe (3) the relationship between the translated text and the theory of grammatical problems found in Arinillah's short stories with the theme of love. Based on the data sources studied, the researcher found grammatical problems in the level of phrases and sentences found in four short story titles with the theme of love. The results of this study are tarkib washfi, tarkib idhafi, atahf mathuf, taukid, simple sentences, complete sentences, and complex sentences in a collection of short stories titled Taufik Hakim Arinillah. The short stories contain Taufik Hakim's philosophical thoughts which are good for the development of today's mindset